Clinical significance of the glucose breath test in patients with inflammatory bowel disease. Issue 6 (June 2015) - Lee, Ji Min; Lee, Kang‐Moon; Chung, Yoon Yung; Lee, Yang Woon; Kim, Dae Bum; Sung, Hea Jung; Chung, Woo Chul; Paik, Chang‐Nyol
Abstract Background and Aim Small intestinal bacterial overgrowth which has recently been diagnosed with the glucose breath test is characterized by excessive colonic bacteria in the small bowel, and results in gastrointestinal symptoms that mimic symptoms of inflammatory bowel disease. This study aimed to estimate the positivity of the glucose breath test and investigate its clinical role in inflammatory bowel disease. Methods Patients aged > 18 years with inflammatory bowel disease were enrolled. All patients completed symptom questionnaires. Fecal calprotectin level was measured to evaluate the disease activity. Thirty historical healthy controls were used to determine normal glucose breath test values. Results A total of 107 patients, 64 with ulcerative colitis and 43 with Crohn's disease, were included. Twenty‐two patients (20.6%) were positive for the glucose breath test (30.2%, Crohn's disease; 14.1%, ulcerative colitis). Positive rate of the glucose breath test was significantly higher in patients with Crohn's disease than in healthy controls (30.2% vs 6.7%, P = 0.014). Bloating, flatus, and satiety were higher in glucose breath test‐positive patients than glucose breath test‐negative patients (P = 0.021, 0.014, and 0.049, respectively). The positivity was not correlated with the fecal calprotectin level. Conclusions The positive rate of the glucose breath test was higher in patients with inflammatory bowel disease, especially Crohn's disease than in healthy controls; gastrointestinal symptoms of patients with inflammatory bowel disease were correlated with this positivity. Glucose breath test can be used to manage intestinal symptoms of patients with inflammatory bowel disease.